Evaluation of products or services offered by non-banking financial institutions by following guidelines given by department of financial institutions and markets - Honey, Umme (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.